Efficacy of Labisia pumila Benth. & Hook. f. and Vernonia amygdalina Delile leaf extracts in alleviating postmenopausal osteoarthritis in rats - Madzuki, Iffah Nadhira (2018)
Osteoarthritis (OA) is a degenerative condition that causes pain and joint stiffness, predominantly in women aged over 60 years. Development of inflammation in OA joint can trigger chondrocytes to produce proteolytic enzymes that cause cartilage degeneration. Therefore, non-steroidal anti-inflammatory drugs (NSAIDs) is the most common medication prescribed for OA to control inflammation and reduce pain. However, NSAIDs eventually exert adverse side effects. Developing alternative medicines for OA from herbal plant that naturally contains anti-inflammatory and antioxidant properties may offer safer treatment. Hereby, the current study was conducted to investigate the efficacy of Labisia pumila and Vernonia amygdalina leaf extracts in alleviating postmenopausal OA. In the preliminary study, the ex vivo explant culture was used to determine the effect of the several plant extracts on inhibition of cartilage degradation under inflammatory conditions induced by interleukin 1 beta (IL-1β). IL-1β plays a major role in OA by stimulating production of inflammatory and catabolic factors. Therefore, the amount of proteoglycan release and nitric oxide (NO) production by the cartilage and chondrocyte morphology were evaluated. Among the extracts, L. pumila and V. amygdalina leaves show the best chondroprotective potential. Hence, L. pumila and V. amygdalina were selected to test on animal for their efficacy. In in vivo study, female Sprague Dawley rats were grouped into (n=8): sham-treated healthy (SHAM), non-treated ovariectomised OA, positive control (diclofenac-treated), treated L. pumila and V. amygdalina leaf extracts at 150 and 300 mg/kg body wt, and combination of extracts, each at 150 mg/kg body wt. The rats were subjected to bilateral ovariectomy and OA was induced by intra-articular injection of monosodium iodoacetate (MIA) (3 mg in 50 μl saline). The SHAM rats received sham-operated and saline solution intra-articular injection. SHAM and non-treated OA rats were administered with deionised water while treatment groups received leaf extracts or diclofenac by oral gavage once daily for 8 weeks. After 8 weeks of treatment, the collected tibiofemoral joint, serum and urine samples were examined for macroscopic, biochemical, joint histological and bone turnover changes. Then, the efficacy of bioactive compounds that present in the extracts; quercetin, caffeic acid, gallic acid, apigenin, kaempferol, kaempferol-3-o-glucoside, myricetin, rutin, and naringin in the exertion of chondroprotective effect was determined in IL-1β pre-treated cartilage. The preliminary study showed the extracts significantly reduced proteoglycan release and NO production by the cartilage. In the animal model, the extracts significantly reduced collagenase activity, inflammation and cartilage catabolism biomarkers and increased expression of cartilage synthesis and bone formation biomarkers. The extracts also mitigated cartilage fibrillation and erosion, subchondral bone lesions, osteophyte formation and epiphyseal/metaphyseal trabecular bone loss. The extracts significantly (p<0.05) increased volume, density, trabecular thickness and separation, and reduced porosity in epiphyseal/metaphyseal bone trabeculum. The study on chondroprotective effect of the extracts’ bioactive compounds by ex vivo study showed that, quercetin, caffeic acid, gallic acid, kaempferol, kaempferol-3-O-glucoside, apigenin, myricetin, rutin and naringin significantly (p<0.05) reduced nitric oxide production and proteoglycan release compared to non-treated cartilage. Caffeic acid, myricetin, naringin and rutin inhibited collagenase activity and prevented inflammation of the cartilage, comparable to diclofenac. This study concluded that both Labisia pumila and Vernonia amygdalina leaf extracts effective in ameliorating cartilage degradation and subchondral bone alteration in the postmenopausal OA, comparable to diclofenac.